The Role of Metamaterials in Advancing Wireless Communications Through Signal Enhancement and Energy Reduction - Zainab N. Mutashar; Sura N. Taraad (Academia Open, 2025)
General Background: Wireless communication systems have become vital in modern life but face persistent challenges including signal degradation, high power consumption, and electromagnetic interference. Specific Background: Recent research highlights metamaterials as a promising solution due to their engineered electromagnetic properties—such as negative permittivity and permeability—that enable unprecedented control over wave propagation. Knowledge Gap: Despite significant theoretical advancements, practical demonstrations of how metamaterials enhance antenna performance in real-world wireless systems remain limited. Aims: This study investigates the integration of metamaterials into antenna structures to improve gain, efficiency, and impedance matching while minimizing reflection and energy loss. Results: Comparative simulations between conventional and metamaterial-enhanced antennas show that at 5.0 GHz, gain increased from 6.1 dBi to 10.4 dBi, efficiency rose from 65.3% to 80.2%, and reflection coefficient dropped from 0.42 to 0.22, confirming superior energy transfer and directivity. Novelty: The research demonstrates how metamaterials function not merely as passive components but as active design tools enabling reconfigurable, frequency-adaptive antenna behavior. Implications: These findings establish metamaterials as essential for next-generation, high-efficiency, and sustainable wireless communication systems.Highlight : The study shows metamaterials improve antenna gain, efficiency, and impedance matching compared to traditional designs. Performance peaks at 5.0 GHz, demonstrating effective resonance and reduced reflection losses. Findings confirm metamaterials’ potential for advanced, efficient wireless communication systems. Keywords : Metamaterials, Antenna Performance, Radiation Efficiency, Reflection Coefficient, Impedance Matching